EDUKASI BAHAYA SMARTPHONE TERHADAP PERKEMBANGAN ANAK DI DUSUN GESING DESA RANDU PITU - Majida Noviyanti; Khotimah, Khusnul; Sari, Dina Fahma (Jurnal Indonesia Mengabdi, 2026)
The use of smartphones has become a daily necessity for people in today's technological era. The numerous features on smartphones support the work of many people. It is undeniable gacorqq that smartphone use has also become a part of the lives of teenagers and even children. With features that present educational content such as letter recognition, reading skills, as well as entertainment and games, children are often exposed to smartphones. In fact, children are still in their developmental stage. Excessive smartphone use can interfere with children's physical, motor, cognitive, social, and emotional gacorqq development. The negative impacts of smartphones need to be understood by children from an early age as a preventive measure. The activities in this report were carried out by providing education about the dangers of smartphone use for children. The method used was socialization through video screenings and material explanations. Evaluation was conducted after the material gacorqq presentation was completed. From the evaluation results, it was found that all the children participants in Gesing, Randu Pitu Village, understood and were aware of the dangers of excessive smartphone use.